Imaginar a Evidência no Alto Douro: projecto para uma casa de férias no terreno do Pinheiro - Mário André Cardoso Vilela (2020)
The project for a holiday house in Alto Douro region, in the Pinheiro land, is the theme that supports this dissertation. The proposal came up in a family context and was born to respond to a request - the house as a structure to harmonize the senses - and allow, by the created circumstances, an effective approach to the practice of architecture called by the confrontation with reality. To give body to this request our intervention strategy defines a projectual narrative that involves the context, client and program and through the analysis and reflection of this elements build an architectural response based on a method of making architecture, to which is associated a cluster of subjects from the sphere of the discipline that structure the bases of the designed response. From the sensory perspective summoned by the client and the search for a way of making project, establishing a close connection between theory and practice, we build our critical vision of architecture due the experiences at Facoltà di Architettura di Ferrara and Escola do Porto.